Immunotherapies targeting CD38 in Multiple Myeloma. (1st November 2016) - Atanackovic, Djordje; Steinbach, Mary; Radhakrishnan, Sabarinath Venniyil; Luetkens, Tim
ABSTRACT: Recently, the monoclonal antibody daratumumab was approved as a single agent for the treatment of patients with relapsed/refractory Multiple Myeloma (MM). Daratumumab is an antibody targeting surface molecule CD38 on myeloma cells and the agent is already widely being used based on its good tolerability and proven efficacy. We believe, however, that the efficacy of this drug and other anti-CD38 monoclonal antibodies can be further improved by combining it with other types of immunotherapies. Furthermore, surface molecule CD38 can be used as a target for immunotherapies other than just naked monoclonal antibodies. In this report, we review the expression pattern of CD38 among normal tissues and in different types of plasma cell dyscrasias including their progenitor cells, minimal residual disease, and circulating tumor cells. We summarize the physiological role of CD38 as well as its role in the pathophysiology of MM and we present the most recent clinical trials using CD38 as a target. In addition, we highlight possible combination immunotherapies incorporating anti-CD38 monoclonal antibodies and we demonstrate alternative immunotherapeutic approaches targeting the same antigen such as CD38-specific chimeric antigen receptor (CAR) T cells.